Penguatan Moderasi Beragama dalam Kehidupan Sosial Masyarakat Berastagi melalui KKN Mahasiswa UINSU 2025 - Rora Rizky Wandini; Teguh Perdana; Amri Yahya; Eliza Mahzura Nasution; Nurazizah Harahap (Pusat Riset dan Inovasi Nasional, 2025)
Strengthening religious moderation is a strategic effort to build a harmonious social life, especially in Berastagi, which is characterized by cultural, religious, and ethnic diversity. Through the Community Service Program (KKN) of UINSU students in 2025, various programs were designed to encourage community participation while raising collective awareness of the importance of religious moderation values. The main programs include a dish soap-making workshop as an economic empowerment initiative, an anti-bullying campaign to instill tolerance, an education awareness campaign to build a quality generation, the creation of educational boards on waste management to preserve the environment, and the “Sapa Desa” (Semangat Aksi Peduli Desa) movement to strengthen social relations. In addition, supplementary programs such as KKN Cerdas, RUMTAr, Gen Q, Spada, along with student involvement in the fruit and flower festival, selling local products, supporting farmers, and fundraising for the Independence Day celebration, further reinforced collaborative roles with the community. These activities are expected to create synergy between students and the people of Berastagi in fostering inclusive attitudes, mutual cooperation, and environmental care, making religious moderation not only a concept but also a real practice in social life.